2005
DOI: 10.1103/physrevlett.95.104302
|View full text |Cite
|
Sign up to set email alerts
|

Interface Thermal Resistance between Dissimilar Anharmonic Lattices

Abstract: We study interface thermal resistance (ITR) in a system consisting of two dissimilar anharmonic lattices exemplified by the Fermi-Pasta-Ulam and Frenkel-Kontorova models. It is found that the ITR is asymmetric; namely, it depends on how the temperature gradient is applied. The dependence of the ITR on the coupling constant, temperature, temperature difference, and system size is studied. Possible applications in nanoscale heat management and control are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
244
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 388 publications
(251 citation statements)
references
References 21 publications
5
244
1
1
Order By: Relevance
“…A scattering boundary method within the lattice dynamic approach [12,13,14] fully considers the atomic structures in the interface; but it can only be applied to ballistic thermal transport. Classical molecular dynamics is another widely used method in phonon transport [15,16,17], which is not accurate below the Debye temperature, and ignores the quantum effect. Only recently the nonequilibrium Green's function method, which originates from the study of electronic transport [18], been applied to study the quantum phonon transport [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A scattering boundary method within the lattice dynamic approach [12,13,14] fully considers the atomic structures in the interface; but it can only be applied to ballistic thermal transport. Classical molecular dynamics is another widely used method in phonon transport [15,16,17], which is not accurate below the Debye temperature, and ignores the quantum effect. Only recently the nonequilibrium Green's function method, which originates from the study of electronic transport [18], been applied to study the quantum phonon transport [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Because the vibrations inducing the structural deformation have a lower frequency than thermal phonons and propagate ballistically in comparison with them, we need an elastic-wave rectifier [31][32][33][34][35][36] rather than the thermal rectifier in order to achieve the expected performance of the nano-device, NEMS and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is found that phonons can be also used to carry and process information [8][9][10][11][12][13][14][15][16][17]. More importantly, different thermal (phononic) devices such as thermal rectifier, thermal transistor, thermal logic gate, and thermal memory, have been conceptualized.…”
mentioning
confidence: 99%